إشكالية كسب العقارات المشهر سنداتها بالتقادم في القانون الجزائري - زرقاط, عيسى (University of Eloued جامعة الوادي, 2021)
يعتبر العقار الثروة الحقيقة للبشر و على أساسها كانت تمنح المكانة الإجتماعية في المجتمعات القديمة ، و قد إنتقلت هذه الفكرة إلى النظم الحديثة ، لدا سعت معظم التشريعات إلى الإعتناء به و قيده في سجلات بأسماء المالكين لكــن و بعد تطور أعداد البشر أصبح نظر قيد العقارات بإسم المالكين غير دقيق و أدى إلى ضياع حقوق الأفراد ظهر نظام آخر أكثر دقة و هو أخذ العقار كمعيار للقيد أو ما يعرف بالسجل العيني للعقارات ، و قد طبق المشرع النظام الأول و أخذ به بموجب الأمر 75/58 المتضمن القانون المدني ( المادة 827 و 828 ق م ) و كذا النصوص التطبيقية لهذين النصين ثم أخذ بفكرة النظام العيني بموجب الأمر 75/74 المتضمن إعداد مسح الأراضي العام و تأسيس السجل العقاري ، و بين تطبيق هذين النصين ظهرت مشاكل كثيرة و تضاربت أحكام القضاء حول مسألة مهمة و هي إمكانية كسب الحقوق العينية المشهرة عن طريق الحيازة ، و من أهم القرار المنشورة في هذا الصدد هو القرار الصادر بتاريخ 15/10/2008 رقم 479371 و النشور في مجلة المحكمة العليا العدد رقم 2 لسنة 2008 و في نشرة القضاة كذلك ، العدد 67 ، و هذا القرار هو محل التعليق الحالي و الذي يكون التعليق عليه ضمن فكرتي الأمن القانوني و الأمن القضائي بإعتبارهما دعامتين مهمتين لتوفير الأمن و السكينة لدى الأفراد في المجتمع . Estate is considered as the real wealth for man. On that basis, social rank was given in ancient societies. This idea has been as well transferded to modern societies. Therfore, most legislations tried to care about estates and registring thier owners’ names. How evere, because of the increase happening in the number of individuals the registeries became harder that led to the loss of the individuals right. So, a new accurate system appeared that dealt with the estate itself as a criterion to the registration i.e the corporeal estate registry. The legislators adopted the old system basing on the order 75/58 that includes civil law ( Art 827, 828 ) as well as thier application texts. Then, they used the new system basing on the order 75/74 that includes the general lands survey and lands registery establishment . When applying the two systems, many problems rose since the judicial decissions contradicted concerning an important issue which is the possibility of gaining publicized corporeal rights through possession. Among the most important decissions, the one on 15/10/2008 number 479371 published in the Supreme Court Journal number 2 of the year 2008 as well in the Judges Paper number 67. This decision is the heart of the comment to be linked to both legal and Judicial securItIes which are the basic element to oblain peace and tranquility in the society.
the problem of gaining the famous real estate statute of limitations in Algerian law« Commentary on the Supreme Court Decision issued on October 15, 2008 No. 479371 »
مقال
Keywords: الشهر ، الحيازة ، التقادم المكسب ، الأمن القانوني ، الأمن القضائي; publicity , possession, gainful limitation, legal securityjudicial security